Analisis Tingkat Kepuasan Mahasiswa Pada Jasa Pelayanan Perpustakaan Universitas Muhammadiyah Jambi - Rian Dani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The main focus of this research is to know and analyze the level of student satisfaction in services at the library at the Muhammadiyah University of Jambi. The data in this study were obtained based on primary data using surveys in collecting data through questionnaires. The number of samples is 100 respondents who are students of Jambi Muhammadiyah University. The variables in the study used 5 dimensions of service quality consisting of reliability, responsiveness, assurance, empathy and tangibles as measured using a Likert scale. The results showed that the importance and quality of service indicated that student respondents in using library services were satisfied with the services provided by the Jambi Muhammadiyah University library. In addition, the results of the analysis in this study showed that the average respondent's answers related to student satisfaction with library services at Jambi Muhammadiyah University were at a value of 4.5, which means that respondents were very satisfied in using library services at Jambi Muhammadiyah University.